Female voices in Babau (Móin-Móin Magazine - Studies in the Art of Puppetry, 2020)
The present work is a partial report on the research being carried out by the puppet theater group Cia Boca de Cena from Paraíba. The research proposes a reflection on the femalevoices that permeate the universe of the popular Northeastern puppet theater, specifically in Paraíba. The data collection was based on participant observation and the work of three puppeteers that was analyzed during their Babau presentations on the “Benedito and João Redondo Through the City Streets” project.